Clinical Significance of Mycobacterium kansasii Isolates from Respiratory Specimens - Moon, Seong Mi (PLoS One, 2015)
The clinical significance of Mycobacterium kansasii respiratory isolates is uncertain. The aims of this study were to determine the clinical relevance of M. kansasii isolates and to identify the clinical features and outcomes of M. kansasii lung disease. We reviewed the medical records of 104 patients from whom at least one respiratory M. kansasii isolate was obtained from January 2003 to July 2014 at Samsung Medical Center, South Korea. Of these 104 patients, 54 (52%) met the diagnostic criteria for nontuberculous mycobacterial lung disease; among them, 41 (76%) patients received antibiotic treatment for a median time of 15.0 months (interquartile range [IQR], 7.0–18.0 months). The remaining 13 (24%) without overt disease progression were observed for a median period of 24.0 months (IQR, 5.0–34.5 months). Patients with M. kansasii lung disease exhibited various radiographic findings of lung disease, including the fibrocavitary form (n = 24, 44%), the nodular bronchiectatic form (n = 17, 32%), and an unclassifiable form (n = 13, 24%). The fibrocavitary form was more common in patients who received treatment (n = 23, 56%), while the nodular bronchiectatic form was more common in patients with M. kansasii lung disease who did not receive treatment (n = 9, 70%). None of the patients with a single sputum isolate (n = 18) developed M. kansasii disease over a median follow-up period of 12.0 months (IQR, 4.0–26.5 months). In total, 52% of all patients with M. kansasii respiratory isolates exhibited clinically significant disease. Moreover, patients with M. kansasii lung disease displayed diverse radiographic findings in addition to the fibrocavitary form. The nodular bronchiectatic form was more common in patients with M. kansasii lung disease with an indolent clinical course. Thus, since the clinical significance of a single M. kansasii respiratory isolate is not definite, strict adherence to recommended diagnostic criteria is advised.